An RNA‐Seq‐based reference transcriptome for Citrus. Issue 3 (11th August 2015) - Terol, Javier; Tadeo, Francisco; Ventimilla, Daniel; Talon, Manuel
Summary: Previous RNA‐Seq studies in citrus have been focused on physiological processes relevant to fruit quality and productivity of the major species, especially sweet orange. Less attention has been paid to vegetative or reproductive tissues, while most Citrus species have never been analysed. In this work, we characterized the transcriptome of vegetative and reproductive tissues from 12 Citrus species from all main phylogenetic groups. Our aims were to acquire a complete view of the citrus transcriptome landscape, to improve previous functional annotations and to obtain genetic markers associated with genes of agronomic interest. 28 samples were used for RNA‐Seq analysis, obtained from 12 Citrus species: C. medica, C. aurantifolia, C. limon, C. bergamia, C. clementina, C. deliciosa, C. reshni, C. maxima, C. paradisi, C. aurantium, C. sinensis and Poncirus trifoliata . Four different organs were analysed: root, phloem, leaf and flower. A total of 3421 million Illumina reads were produced and mapped against the reference C. clementina genome sequence. Transcript discovery pipeline revealed 3326 new genes, the number of genes with alternative splicing was increased to 19 739, and a total of 73 797 transcripts were identified. Differential expression studies between the four tissues showed that gene expression is overall related to the physiological function of the specific organs above any other variable. Variants discovery analysis revealed the presence of indels and SNPs in genes associated with fruit quality and productivity. Pivotal pathways in citrus such as those of flavonoids, flavonols, ethylene and auxin were also analysed in detail.